Investigation regarding the effectiveness of nitrogen sources and concentration on plant characteristics in tomato (Lycopersicon Esculentum) - Mohamed Mohamoud Adow, 1985- (2013)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2013